ANALISIS KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN TEMATIK KELAS III B DAN III C DI SDN X JAKARTA BARAT - Kusumawardani, Siska (Jurnal Holistika, 2024)
This research only focuses on teacher pedagogical competence in teaching thematic for third grade III B and III C of SDN X West Jakarta. Pedagogic competence is an ability that must be mastered by teachers in carrying out their professional duties, namely in managing, implementing, and evaluating learning. The aims of this study were to: (1) describe the pedagogic competence of teachers in thematic learning for class III B and III C, (2) describe the inhibiting factors of teachers in implementing thematic learning for class III B and III C, and (3) describe the supporting factors for teachers in the implementation of thematic learning class III B and III C. The method used is qualitative research using a qualitative descriptive approach. Data collection techniques were carried out by means of observation, interviews and documentation. Data analysis techniques are carried out by collecting data in the field, data reduction, data presentation, and drawing conclusions. The validity of the data is carried out through credibility tests, namely source triangulation and member checking. The results of this study indicate that the pedagogical competence of class III B and III C teachers in the implementation of thematic learning in class as a whole is good. Teachers can understand the characteristics of students, are able to master learning theory and learning principles, teachers carry out curriculum development and educational learning activities, develop students' potential, and carry out assessments and evaluations. From the results, the percentage of teacher competency obtained is still categorized as low, namely 65%. Teachers need to improve the quality of their pedagogical competence in order to become professional teachers. Teachers are expected to be able to maintain and improve their pedagogical competencies so that thematic learning can run optimally.